A Bibliometric Study of Community Resilience Research in G20 Countries - Banerjee, Sudip; Chakrabarti, Kaustuv (Journal of Data Science, Informetrics, and Citation Studies)
The present bibliometric study examines the publication outputs on community resilience among G20 countries as cited in the Scopus database over the last 10 years, 2013-2022. Research in community resilience among G20 countries and other allied areas was analyzed in terms of their year wise growth, authorship pattern, collaborations, relative research effort, citation impact, document type preference, most productive authors and most popular journals Beside this, the study tried to rank top ten prolific authors and popular journals according to their Citations per Publication. The study revealed that from 2013 to 2022 the publication outputs on community resilience among G20 countries showed consistent growth and resulted in 3570 publications. Initially, in 2013, only 143 publications were published and in 2022 it had increased to 661 publications. The USA is the leader in Community Resilience Research with 1351 publications but their CPP and impact are not so higher compare to the average. The degree of collaboration displayed its strength in multi-authored collaborative publications. Articles are the most preferred type of document. 81.46% of publications remain cited and only 18.54% of publications remain uncited till now. A total of 52146 citations have been received by 3570 publications and CPP is 14.61. In terms of p-index, the top three countries are USA, UK and Australia. Being the world's leading economies, the G20 countries can take leadership in future research on community resilience. This work can provide valuable insights into research trends and help identify key themes and topics in the field.
Keywords: Bibliometrics; Community Resilience; Research; G20 Countries.